Factors influencing the nutritional status of adolescents during the COVID-19 pandemic: A cross-sectional study - Riri Novayelinda; Oswati Hasanah; Syafrida Hanum (School of Health Sciences Al-Ma'arif, 2026)
Background: The COVID-19 pandemic substantially altered adolescents’ daily routines, including eating habits, physical activity, and sleep patterns, all of which may influence nutritional status. Evidence from Indonesia remains limited, particularly regarding the simultaneous contribution of these behavioral factors during periods of prolonged social restriction. Objective: This study aimed to examine the associations between dietary patterns, physical activity, sleep quality, and nutritional status among adolescents in Pekanbaru, Indonesia, during the COVID-19 pandemic. Methods: A cross-sectional study was conducted from June to November 2021 among 75 adolescents aged 15–18 years in Pekanbaru, Riau Province, Indonesia. Participants were recruited through convenience sampling using school and alumni WhatsApp groups. Data were collected online using a structured self-administered questionnaire that included a Food Frequency Questionnaire for dietary patterns, the Indonesian version of the Physical Activity Questionnaire for Adolescents (PAQ-A), and the Pediatric Daytime Sleepiness Scale (PDSS) for sleep-related problems. Nutritional status was assessed using self-reported weight and height to calculate body mass index (BMI), which was then classified into underweight, normal, and overweight categories. Descriptive statistics and chi-square tests were used for data analysis, with statistical significance set at p < 0.05. Results: Of the 75 participants, most were 17 years old (40.0%) and female (70.7%). Overall, 68.0% had normal nutritional status, 18.7% were overweight, and 13.3% were underweight. Chi-square analysis showed significant associations between dietary patterns and nutritional status (p = 0.001), sleep quality and nutritional status (p = 0.001), and physical activity and nutritional status (p = 0.001). These findings indicate that unhealthy dietary patterns, poor sleep-related functioning, and lower physical activity were associated with abnormal BMI categories among adolescents. Conclusion: Dietary patterns, physical activity, and sleep quality were significantly associated with adolescent nutritional status during the COVID-19 pandemic. These findings highlight the importance of integrated behavioral screening and adolescent health interventions targeting diet, movement, and sleep to support optimal nutritional outcomes.